Facile Fabrication of Redox‐Responsive Covalent Organic Framework Nanocarriers for Efficiently Loading and Delivering Doxorubicin. Issue 4 (1st January 2020) - Liu, Shuai; Yang, Jumin; Guo, Ruiwei; Deng, Liandong; Dong, Anjie; Zhang, Jianhua
Abstract: Covalent organic frameworks (COFs) as drug delivery systems have shown great promise, but their pharmaceutical applications are often limited by complex building blocks, tedious preparations, irregular shape, and uncontrolled drug release within target cells. Herein, a facile strategy is developed to prepare PEGylated redox‐responsive nanoscale COFs (denoted F68@SS‐COFs) for efficiently loading and delivering doxorubicin (DOX) by use of FDA‐approved Pluronic F68 and commercially available building blocks. The obtained F68@SS‐COFs with controlled size, high stability, and good biocompatibility can not only achieve a very high DOX‐loading content (about 21%) and very low premature leakage at physiological condition but can also rapidly respond to the tumor intracellular microenvironment and efficiently release DOX to kill tumor cells. Considering the readily available raw materials, simple preparation process, and desirable redox‐responsiveness, the strategy provided here opens up a promising avenue to develop well‐defined COFs‐based nanomedicines for cancer therapy. Abstract : Covalent organic frameworks (COFs) show great promise for pharmaceutical applications. Herein, a facile strategy is designed to prepare a PEGylated redox‐responsive COFs‐based nanosystem (F68@SS‐COFs) for efficiently loading and delivering DOX from easily available raw materials. The F68@SS‐COFs with well‐controlled shape can achieve high drug loading, extracellular stability, excellent biocompatibility, and intracellular GSH‐triggered drug release, exhibiting great potential for anticancer drug delivery.